2017
DOI: 10.1186/s12885-017-3178-8
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue fibrosis in human cancer cachexia: the role of TGFβ pathway

Abstract: BackgroundCancer cachexia is a multifactorial syndrome that dramatically decreases survival. Loss of white adipose tissue (WAT) is one of the key characteristics of cachexia. WAT wasting is paralleled by microarchitectural remodeling in cachectic cancer patients. Fibrosis results from uncontrolled ECM synthesis, a process in which, transforming growth factor-beta (TGFβ) plays a pivotal role. So far, the mechanisms involved in adipose tissue (AT) re-arrangement, and the role of TGFβ in inducing AT remodeling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 65 publications
9
73
0
6
Order By: Relevance
“…A recent study showed that up‐regulation of HIF‐1α and TGF‐β pathways contributes to cell survival and chemoresistance in colorectal cancer . In line with these observations, we previously demonstrated that the adipose tissue, while playing an important role in systemic inflammation by secreting cytokines and chemokines, undergoes extensive fibrosis in CAC and that one such effect is partly mediated by TGF‐β, which causes the rearrangement of extracellular matrix components and leads to severe tissue architecture disruption in cancer patients with cachexia . TGF‐β signalling promotes fibroblast to myofibroblast transdifferentiation by inducing the expression of α‐SMA, a specific myofibroblast marker.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…A recent study showed that up‐regulation of HIF‐1α and TGF‐β pathways contributes to cell survival and chemoresistance in colorectal cancer . In line with these observations, we previously demonstrated that the adipose tissue, while playing an important role in systemic inflammation by secreting cytokines and chemokines, undergoes extensive fibrosis in CAC and that one such effect is partly mediated by TGF‐β, which causes the rearrangement of extracellular matrix components and leads to severe tissue architecture disruption in cancer patients with cachexia . TGF‐β signalling promotes fibroblast to myofibroblast transdifferentiation by inducing the expression of α‐SMA, a specific myofibroblast marker.…”
Section: Introductionsupporting
confidence: 57%
“…Gene expression of COL1A and COL3A was significantly increased in CC, relative to WSC ( Figure A; P = 0.03 and P = 0.05, respectively). Vimentin (a type III intermediate filament related to cellular motility) expression was increased in the tumour of CC ( Figure A; P = 0.02), and this feature was shown to be correlated with the numbers of activated fibroblasts in cachexia . Recently, the metastatic potential of cancer cell has been correlated with cachexia development .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Abdominal subcutaneous adipose depots of lean cachectic subjects bearing gastrointestinal cancers displayed extensive adipose ECM remodeling, including a dramatic increase in deposition of collagens I, III, and VI as well as elastin and fibronectin (11). These changes were associated with increased myofibroblast content and elevated activation of TGF-β/SMAD signaling pathways (11). As described later in the Adipocytes and adipocyte-cancer interactions section , cancer-associated cachexia is also associated with metabolic dysfunction in adipocytes, which may be mediated in part by ECM modifications.…”
Section: Microenvironmental Links Between Adipose Tissue and Cancermentioning
confidence: 99%